JAK-STAT Signal Inhibition Regulates Competition in the Drosophila Testis Stem Cell Niche - Issigonis, Melanie (2009)
Adult stem cells often reside in local microenvironments, or niches. Although niches can contain multiple types of stem cells, the coordinate regulation of stem cell behavior is poorly understood. In the Drosophila testis, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling is directly required for maintenance of the resident germline and somatic stem cells. We found that the JAK-STAT signaling target and inhibitor Suppressor of cytokine signaling 36E (SOCS36E) is required for germline stem cell maintenance. SOCS36E suppresses JAK-STAT signaling specifically in the somatic stem cells, preventing them from displacing neighboring germline stem cells in a manner that depends on the adhesion protein integrin. Thus, in niches housing multiple stem cell types, negative feedback loops can modulate signaling, thereby preventing one stem cell population from outcompeting the other.